Stakeholder involvement in adaptive goose management; case studies and experiences from Norway - Tombre, Ingunn M.; Eythórsson, Einar; Madsen, Jesper (Ornis Norvegica, 2013)
Two Svalbard-breeding goose populations, the pink-footed goose Anser brachyrhynchus and the barnacle goose Branta leucopsis, have, over the last decades, increased in numbers and expanded in distribution. At spring-staging sites in Norway, conflicts with agriculture are significant as the geese feed on cultivated fields, with negative consequences for the farmers. In the present paper we give an overview of relevant stakeholders in these goose-agriculture conflicts and share some of our experiences when involving stakeholders and users in a dynamic and adaptive process. The paper demonstrates how researchers can engage in the management process at different levels, in order to facilitate a process towards an adaptive co-management in an environment of conflicting interests. The framework described may be used for threatened bird species and situations where there are conflicts between wildlife stakeholders such as management agencies, conservation interests, hunting and agriculture.